Moving teachers to Malawi’s remote communities: A data-driven approach to teacher deployment - Asim, Salman; Chimombo, Joseph; Chugunov, Dmitry; Gera, Ravinder (International Journal of Educational Development, 2019)
There are severe geographical disparities in pupil-teacher ratios (PTR) across Malawi, with most teachers concentrated near commercial centers and in rural schools with better amenities. Most of the variation in PTR is concentrated in small sub-district areas, suggesting a central role for micro-geographic factors in teacher distribution. Employing administrative data from several government sources, regression analysis reveals that school-level factors identified by teachers as desirable are closely associated with PTR, including access to roads, electricity, and water, and distance to the nearest trading center, suggesting a central role for teachers’ interests in PTR variation. Political economy network mapping reveals that teachers leverage informal networks and political patronage to resist placement in remote schools, while administrative officials are unable to stand up to these formal and informal pressures, in part because of a lack of reliable databases and objective criteria for the allocation of teachers. This study curates a systematic database of the physical placement of all teachers in Malawi and links it with data on school facilities and geo-spatial coordinates of commercial centers. The study develops a consistent and objective measure of school remoteness, which can be applied to develop policies to create rules for equitable deployments and targeting of incentives. Growing awareness of disparities in PTRs among district education officials is already showing promising improvements in targeting of new teachers. Simulation results of planned policy applications show significant potential impacts of fiscally-neutral approaches to targeted deployments of new cohorts, as well as retention of teachers through data-calibrated incentives.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2018.12.002 2339240:7QKQHXG2 2405685:GWKND7GG
Keywords: Data-driven model; Deployments; Malawi; Political economy; Schools; Teachers

Malawi Education Sector Analysis - Malawi Ministry of Education, Science, and Technology, Malawi (Government of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:D5NERCHI 2405685:UKTVQWTU

Ministry of Education, Science and Technology – Policy Reforms - Malawi Ministry of Education, Science and Technology (2019)
The Malawi Public Sector Reforms Management Unit exists to catalyse, drive and facilitate public sector reforms in Malawi. The reforms are implemented in Government ministries, departments and agencies (MDAs), local councils, parastatal organizations and constitutional bodies.
KerkoCite.ItemAlsoKnownAs: 2339240:CVBB75DU 2405685:Z4Z43LCT

Malawi Economic Outlook - African Development Bank (African Development Bank - Building today, a better Africa tomorrow, 2019)
Recent macroeconomic and financial developments Growth in Malawi’s economy decelerated in 2020 to 1.7% from 5.7 % in 2019. The slowdown in GDP growth was driven by the outbreak of COVID–19, which necessitated a partial lockdown of the economy, resulting in subdued economic activities—mainly in tourism, the accommodation and food subsectors, transportation, and agriculture. Other sectors affected by disruptions from the COVID–19 pandemic disruptions were manufacturing and mining and quarrying.
Publisher: African Development Bank Group KerkoCite.ItemAlsoKnownAs: 2339240:QAWBXWAY 2405685:XKHR65LI

Unlocking Talent Through Technology Malawi - VSO (2019)
KerkoCite.ItemAlsoKnownAs: 2339240:5A6J5JZU 2405685:LPRCAQI5

GPE 2020 Country-level Prospective Evaluations. Malawi - Smith, Prepared Matthew; Fenning, Christine (Global Partnership for Education (GPE), 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:9ABNU7B8 2405685:DQGKVE9A
Keywords: ⛔ No DOI found

Research to Investigate Low Learning Achievement in Early Grade Numeracy (Standards 1–4) in Malawi: The victory of form over substance - Brombacher, Arnout (HEART, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:M7DRE98S 2405685:AIUSUUNA

Complexity and Considerations in Delivering Adaptive Learning Digital Services - Proctor, Jamie (EdTech Hub, 2019)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4561896 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4561896 2339240:M4PBAXK6 2405685:XU7B7DHZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

2018 Population and Housing Census - National Statistics Office (Government of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:UXWI3QF6 2405685:4KBEPZKW

Interactive apps prevent gender discrepancies in early-grade mathematics in a low-income country in sub-Saharan Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
Globally, gender differences are reported in the early acquisition of reading and mathematics as girls tend to outperform boys in reading, whereas boys tend to outperform girls in mathematics. This can have long-term impact resulting in an under-representation of girls in Science, Technology, Engineering and Mathematics subjects. Recent research suggests that sociocultural factors account for differences across genders in the acquisition of these foundational skills. In this study, we investigated whether a new technology-based intervention, that included activities accessible to both boys and girls, can reduce gender differences from emerging during the early primary school years. The novel instructional method used in this study employed apps developed by onebillion© delivered individually through touch-screen tablets. Over a series of experiments conducted in Malawi, a low-income country in sub-Sahara Africa, we found that when children were exposed to standard pedagogical practice typical gender differences emerged over the first grade (Experiment 1). In contrast, boys and girls learnt equally well with the new interactive apps designed to support the learning of mathematics (Experiment 2) and reading (Experiment 3). When implemented at the start of primary education, before significant gender discrepancies become established, this novel technology-based intervention can prevent significant gender effects for mathematics. These results demonstrate that different instructional practices influence the emergence of gender disparities in early mathematics. Digital interventions can mitigate gender differences in countries where standard pedagogical instruction typically hinders girls from acquiring early mathematical skills at the same rate as boys. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=55x-6hhAY9M&feature=youtu.be
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/desc.12864 shortDOI: 10/gf62gt KerkoCite.ItemAlsoKnownAs: 10.1111/desc.12864 10/gf62gt 2339240:EKD2MTYC 2339240:N2E537Q2 2339240:YWPSSQ8L 2405685:7V9ZSCAY 2405685:HVQMEY57 2405685:LTX7M323
Keywords: education; gender inequity; mathematics; reading; tablet technology

Interactive apps prevent gender discrepancies in early-grade mathematics in a low-income country in sub-Sahara Africa - Pitchford, Nicola J.; Chigeda, Antonie; Hubber, Paula J. (Developmental Science, 2019)
Globally, gender differences are reported in the early acquisition of reading and mathematics as girls tend to outperform boys in reading, whereas boys tend to outperform girls in mathematics. This can have long-term impact resulting in an under-representation of girls in Science, Technology, Engineering and Mathematics subjects. Recent research suggests that sociocultural factors account for differences across genders in the acquisition of these foundational skills. In this study, we investigated whether a new technology-based intervention, that included activities accessible to both boys and girls, can reduce gender differences from emerging during the early primary school years. The novel instructional method used in this study employed apps developed by onebillion© delivered individually through touch-screen tablets. Over a series of experiments conducted in Malawi, a low-income country in sub-Sahara Africa, we found that when children were exposed to standard pedagogical practice typical gender differences emerged over the first grade (Experiment 1). In contrast, boys and girls learnt equally well with the new interactive apps designed to support the learning of mathematics (Experiment 2) and reading (Experiment 3). When implemented at the start of primary education, before significant gender discrepancies become established, this novel technology-based intervention can prevent significant gender effects for mathematics. These results demonstrate that different instructional practices influence the emergence of gender disparities in early mathematics. Digital interventions can mitigate gender differences in countries where standard pedagogical instruction typically hinders girls from acquiring early mathematical skills at the same rate as boys. A video abstract of this article can be viewed at https://www.youtube.com/watch?v=55x-6hhAY9M&feature=youtu.be
20 citations (Crossref) [2024-04-29] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/desc.12864 KerkoCite.ItemAlsoKnownAs: 10.1111/desc.12864 2339240:NRXHX74Y 2405685:Q9BQA7GE
Keywords: education; gender inequity; mathematics; reading; tablet technology; ⛔ No INSPIRE recid found

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Education Sector Analysis - Ministry of Education, Science, and Technology (Government of the Republic of Malawi, 2019)
KerkoCite.ItemAlsoKnownAs: 2339240:F2455KDU 2405685:WFQZZHPI

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
previousshortDOI: 10/ghgk6v previousDOI: 10.5281/zenodo.3346903 EdTechHub.Source: 2405685:3BG5X7VG EdTechHub.Source: <this> shortDOI: 10/ghgk6v KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3346903 10.53832/edtechhub.0017 10/ghgk6v 2129771:FLGEYF22 2339240:SZ4GSDD6 2405685:3BG5X7VG
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
previousshortDOI: 10/ghgnfm previousDOI: 10.5281/zenodo.3523935 EdTechHub.Copy: 2129771:NB3WMPDJ shortDOI: 10/ghgnfm KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3523935 10.53832/edtechhub.0016 10/ghgnfm 2129771:NB3WMPDJ 2339240:B5AIHWDZ 2405685:2GC35JLV 2405685:LSEETV6K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode